2022
DOI: 10.3390/ijms23105404
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mouse Models of Alzheimer’s Disease: An Integrative Analysis

Abstract: Alzheimer’s disease (AD) constitutes the most prominent form of dementia among elderly individuals worldwide. Disease modeling using murine transgenic mice was first initiated thanks to the discovery of heritable mutations in amyloid precursor protein (APP) and presenilins (PS) genes. However, due to the repeated failure of translational applications from animal models to human patients, along with the recent advances in genetic susceptibility and our current understanding on disease biology, these models have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 392 publications
0
49
0
Order By: Relevance
“…Several transgenic mouse models of AD have been created by the introduction of human FAD mutations in the APP and genes PSEN1/2 genes of the mouse genome. This introduction gives rise to the development of cerebral amyloid beta (Aβ) pathology in mice [ 35 , 36 ]. Conversely, no definitive human mutation in tau has yet been linked to AD; however, efforts have been made to develop transgenic mice expressing human microtubule-associated protein tau (hMAPT) with frontotemporal dementia-causing mutations [ 37 , 38 ].…”
Section: Alzheimer´s Disease Pathology Hallmarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Several transgenic mouse models of AD have been created by the introduction of human FAD mutations in the APP and genes PSEN1/2 genes of the mouse genome. This introduction gives rise to the development of cerebral amyloid beta (Aβ) pathology in mice [ 35 , 36 ]. Conversely, no definitive human mutation in tau has yet been linked to AD; however, efforts have been made to develop transgenic mice expressing human microtubule-associated protein tau (hMAPT) with frontotemporal dementia-causing mutations [ 37 , 38 ].…”
Section: Alzheimer´s Disease Pathology Hallmarksmentioning
confidence: 99%
“…Mutations to both APP and PSEN1/ PSEN2 have been shown to result in mouse models that develop faster and more aggressive amyloidosis than the single APP mutation models as well as earlier cognitive decline and neuronal loss [ 36 ]. PS/APP is a double transgenic model with APP Swedish and PSEN1 M146L mutations.…”
Section: Alzheimer´s Disease Pathology Hallmarksmentioning
confidence: 99%
“…A spate of molecular neurobiology research identified inheritable mutations of the APP gene directly responsible for familial AD (Campion et al, 1999). In singletransgenic or double-transgenic animal models (Tg animal) of APP mutations of familial AD (Borchelt et al, 1997;Carlson et al, 1997;Games et al, 1995), the histopathological progression of cerebral amyloid-β (Aβ) deposition was reproduced, and the synaptic damage, neuronal loss and memory impairment of the AD patients can again be found in the animal models of AD, but NFTs, the major neuropathological features of AD brain, cannot be reproduced in the Tg animals (Pang et al, 2022;Sanchez-Varo et al, 2022;Sasaguri et al, 2017). The information that was obtained from the collected human brain tissues was indispensable for uncovering the mechanisms of neuropsychiatric disorders.…”
Section: Human Brain Tissue As a Cornerstone Of Neurosciencementioning
confidence: 99%
“…Cellular culture and animal models cannot always mimic every aspect of human disease, especially mental and neuropsychiatric disorders (Duyckaerts et al, 2008). For example, monogenic and biogenic APP-based AD mouse models involving mutant APP or mutant APP and presenilin (PS) 1 or presenilin 2 gene expression model the typical amyloid-β (Aβ) accumulation of familial and sporadic AD in humans, but neuropathological changes in NFTs have not been found (Carlson et al, 1997;Duyckaerts et al, 2008;Sanchez-Varo et al, 2022;Sasaguri et al, 2017;Webster et al, 2014). Although current Tg-mice of AD models reproduce the Aβ plaques that were described in human AD brains to some extent, the morphological variety and diversity of Aβ plaques are wider in human samples.…”
Section: Human Brain Tissue As a Cornerstone Of Neurosciencementioning
confidence: 99%
“…There has been much work on animal models [ 117 , 118 , 119 , 120 ], cellular models, [ 121 , 122 , 123 , 124 , 125 ] and computational/mathematical models [ 126 , 127 , 128 , 129 ] of dementia. However, none of these has captured all of the critical elements involved in the pathogenesis of the dementias and so cannot generate the sought-after answers.…”
Section: Specific Challengesmentioning
confidence: 99%